MOVING ABSTRACTION: OPENING IN ALEXANDER CALDER’S MOBILES AND PIET MONDRIAN’S TRANSATLANTIC PAINTINGS (Palíndromo, 2019)
The present essay intends to showcase a comparative relation between the work of two artists at the vanguard of abstract production: Piet Mondrian in painting and Alexander Calder in sculpture. In several studies on the development of Calder’s work, Mondrian’s role is restricted to the reception of the former in his studio, in 1930: when Calder came across the colorful rectangles and the absence of ornamentation, he suggested movement to all of that, which culminated in a series of abstract experiments that would quickly become his known Mobiles. The discrepancy between both of their artistic theories – on one hand Mondrian’s inflexibility in following the neoplastic propositions, and on the other Calder’s light fluency – are not enough to cancel the stylistic similarities of their artwork. Therefore, this research em-phasizes how their kinship goes beyond Calder’s awakening to non-figurative art, while it relies on Umberto Eco’s open work concept to showcase how their unusual genius, both Apollonian and Dionysian, potentiates their artwork.
Keywords: abstract painting; abstract sculpture; open work